Lighting environment predicts the relative abundance of male colour morphs in bluefin killifish (Lucania goodei) populations. - Fuller, Rebecca C (2002)
Animal communication occurs when an animal emits a signal, the signal is transmitted through the environment, and then detected by the receiver. The environment in which signalling occurs should govern the efficacy of this process. In this study, I examine the relationship of lighting environment (light transmission and tree cover), location and the relative abundances of male colour morphs across seven drainages and 30 populations in the bluefin killifish, Lucania goodei. I found that males with blue anal fins were more common in populations with low transmission of ultraviolet (UV) and blue wavelengths. By contrast, males with red anal fins (and to a lesser extent, males with yellow anal fins) were more common in populations with high transmission of UV and blue wavelengths. High UV-blue light transmission should create a blue visual background and may make blue males less conspicuous and red males more conspicuous to conspecifics. Colour contrast with the visual background may be more important than total brightness of the colour pattern. These results indicate that natural selection for effective intraspecific communication drives the relative abundance of male colour morphs in different lighting habitats.